(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article highlights the issues of ecological culture, the formation of a healthy lifestyle and spiritual and moral education of students. The formation of ecological culture and spiritual and moral education of students is theoretically based on the essence of the content